The influence factors on choice behavior regarding green products based on the theory of consumption values - Lin, Pei-Chun; Huang, Yi-Hsuan (Journal of cleaner production, 2012)
This study applies the theory of consumption values to determine the influence factors on consumer choice behavior regarding green products, and examines whether there are significant differences in consumption values and choice behavior between consumers with different outlooks on environmental concerns. One-way analysis of variance and multiple regression is used to assess data collected by a questionnaire survey. The results indicate that consumers with high environmental concern support green products more, and show greater readiness to choose them. This study concludes that the main influence factors on consumer choice behavior regarding green products include psychological benefit, desire for knowledge, novelty seeking, and specific conditions, and do not include functional values, price and quality. This study contributes to preliminary but vital insights in effective promotion of green products.